Planejamento em saúde bucal no município de João Pessoa, Estado da Paraíba: o cirurgiãodentista enquanto protagonista da atenção básica - Cavalcanti, Yuri Wanderley; Júnior, Ronaldo Lira; Delmondes, Laryza Neves; Prado, Rosana Leal do [UNESP]; Padilha, Wilton Wilney Nascimento (Universidade Estadual de Maringa, 2012)
The aim was to identify the perception of Oral Health Planning (OHP) of basic care (BC) dental surgeons (DSs) in João Pessoa, Paraíba State, Brazil. Seventeen BC DSs from João Pessoa were interviewed. A qualitative analysis was performed using the Discourse of the Collective Subject (DCS) methodology. DCS obtained: Impact - My work is effective when the user's need remains at the BC. Social Control - The population participates in the organization of promotional activities, but I think it doesn't have enough maturity to opine on OHP. OHP Basis and Organization - The OHP has a diverse organization and is based on user needs. It can be concluded that the knowledge of the DSs on OHP is varied. There is limited understanding about problem-solving. Social control is considered incipient and weak. It is understood that the organization of the local OHP assumes a diverse character and should be based on user demands.
Oral health planning in João Pessoa municipality, PR State: dental surgeons as protagonists of basic care
Keywords: Basic health care; Health planning; Oral health; Brazil; clinical decision making; clinical practice; control strategy; dental health education; dentist; health care planning; health program; health promotion; human; mouth hygiene; physician attitude; public health service; qualitative analysis; social control